2019
DOI: 10.1093/rheumatology/kez001
|View full text |Cite
|
Sign up to set email alerts
|

A novel glucocorticoid-free maintenance regimen for anti-neutrophil cytoplasm antibody–associated vasculitis

Abstract: Objectives. Glucocorticoids (GCs) are a mainstay of treatment for patients with ANCA-associated vasculitis (AAV) but are associated with significant adverse effects. Effective remission induction in severe AAV using extremely limited GC exposure has not been attempted. We tested an early rapid GC withdrawal induction regimen for patients with severe AAV.Methods. Patients with active MPO-or PR3-ANCA vasculitis or ANCA-negative pauci-immune glomerulonephritis were included. Induction treatment consisted of two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 28 publications
1
31
0
4
Order By: Relevance
“…There is still significant morbidity in vasculitis patients associated with current treatments, and there are also forms of CGN such as IgA nephropathy for which we have limited effective treatments. Glucocorticoid therapy is associated with significant long-term morbidity and recent trials in CGN have been designed to address the need for steroid minimisation (PEXIVAS, CLEAR, ADVOCATE and our recent steroid free maintenance AAV cohort study) [44][45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…There is still significant morbidity in vasculitis patients associated with current treatments, and there are also forms of CGN such as IgA nephropathy for which we have limited effective treatments. Glucocorticoid therapy is associated with significant long-term morbidity and recent trials in CGN have been designed to address the need for steroid minimisation (PEXIVAS, CLEAR, ADVOCATE and our recent steroid free maintenance AAV cohort study) [44][45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of comparative data on the use of either cyclophosphamide or rituximab in patients with low glomerular filtration rate (for example, <20 ml/min/1.73 m 2 ), with a lower dose of cyclophosphamide together with rituximab being used in the RITUXVAS trial 198 . The use of this combination is controversial and may confer an additional risk of infection 199 .…”
Section: Other Immunosuppressive or Immunomodulating Drugsmentioning
confidence: 99%
“…A two centre cohort study has reported 49 patients who received combination treatment with rituximab and low-dose IV cyclophosphamide and a rapid glucocorticoid taper, approximating a total steroid dose of 1 g administered over 2 weeks. Ninety percent of patients were in sustained remission at 12 months without requiring additional glucocorticoids, and there were reduced rates of serious infections and new onset diabetes compared with historical EUVAS controls [50]. There is also potential for novel therapeutics to replace steroids entirely.…”
Section: Pexivas and Steroidsmentioning
confidence: 99%